Przesłanki decyzji rządu Stanleya Baldwina o zerwaniu stosunków dyplomatycznych ze Związkiem Sowieckim 24 maja 1927 r. - Piątek, Justyna (Acta Universitatis Lodziensis. Folia Historica, 2010)
The British-Soviet relations were established in 1924 under the Labor Party’s rules. In the same year, so called “Campbell case” and the “Zinoviev letter”, begun the Conservative Party’s campaign against communist propaganda. From 12th to 14th May 1927 Metropolitan Police and the Scotland Yard were searching the building at Moorgate 49 which was the headquarter of the All- Russian Cooperative Society Ltd. (Arcos) and Russian Trade Delegation to catch Soviets redhanded. The raid was a violation of the British-Soviet Agreement of 1921; breaking Soviet’s rights and privileges. This action was taken on account of circumstantial evidences of the espionage practiced in this building, mainly the missing document from War Office, and, unofficially, some secret documents collected by Government Codes and Cipher School (GC&CS) Formally the diplomatic rupture with USSR on 24th May 1927 and expulsion of the trade delegation were because of exhibits found by searching house at Moorgate 49. It is significant that the missing document was never found and the confiscated materials were not satisfying. To justify the Government’s decision a white paper was published. The book contained intercepted, secret Soviet telegrams what consequently affectcd the GC&CS work adversely. In fact the reasons of severance of diplomatic relations were more complicated. First of all USSR was interfering into Chinese matters and there promoted subversion and espionage. Moreover the inconvenient trade agreement and an increase of the Labor Party’s popularity were highly uncomfortable for the Stanley Baldwin’s Government. In the conclusion the meaning of Soviet espionage was to camouflage politically motivated decisions and, what is the most important, it have been determining the Government's moves in the entire period of Conservative’s rules.